Export Competitiveness and FDI Performance across the Regions of the Russian Federation - Dairabayeva, Karlygash; Ferrantino, Michael J.; Portugal-Perez, Alberto; Schmidt, Gabriela (World Bank, Washington, DC, 2016)
The Russian Federation's regions not only have highly uneven degrees of development, they also have very uneven degrees of foreign orientation. Regions with the highest foreign orientation--exports of goods per capita or inbound foreign direct investment per capita—almost across the board have the highest standard of living; and those with the lowest foreign orientation generally have the lowest. In this paper, the Russian federal regions are grouped into three categories--lagging, middle-range, and leading--according to real per capita gross regional product. Leading regions seem to be those specialized in mineral exports; lagging regions are not. In addition, the richest regions tend to have high per capita exports, high foreign direct investment, or both; middle-range regions with relatively higher incomes often have high per capita non-mineral exports. Russia's lagging regions have much more tenuous international engagements than the rest of Russia in exports and foreign direct investment. These findings suggest that foreign orientation is an important determinant of socioeconomic development and could be an important item on Russia's regional policy agenda. Such policies might have a variety of objectives: (1) earning income (export goods in which Russia has traditionally had a comparative advantage); (2) diversification and economic stability (minimize risk from drops in oil prices or crises in individual markets and add exports for which demand is likely to be steady over the medium term); (3) technological upgrading (move to more sophisticated goods with greater innovation content); and (4) regional development (promote the uplift of lagging regions). Each of these motives has a different profile of goods exported, regions, and most closely associated destination markets.